The Experience of Family Caregivers Living with Advanced Cancer Patients - Wanda Kiyah George Albert; Zulkarnain Ahmed Hatta; Adi Fahrudin (Asian Social Work Journal, 2017)
This article is based on literature review regarding family experiences in taking care of advanced cancer patients. Four aspect of the family cancer experience were identified from the literature: stress, burden, self-efficacy and self-esteem. The most developed body of literature documents due to family responses towards burden and stressful experience in caregiving was caused by their unprepared and inability to provide care and lack of support from other family members and health care providers. Caregiver’s burden and stressful experiences reporting would be the strongest relationship for lower levels of self-efficacy and self-esteem. The results of this review suggest that more research is needed on family experience and consider interpersonal support as a potential source or moderator variable in enhance family quality of life.